Activation of the G protein‐coupled sulfakinin receptor inhibits blood meal intake in the mosquito Aedes aegypti - Jiang, Linlong; Xie, Xiao Bing; Zhang, Lei; Tang, Yu; Zhu, Xiaojing; Huang, Yuqi; Hong, Yue; Hansson, Bill S.; Cui, Zong Jie; Han, Qian (The FASEB journal, 2024)
Little is known about the blood‐feeding physiology of arbovirus vector Aedes aegypti although this type of mosquito is known to transmit infectious diseases dengue, Zika, yellow fever, and chikungunya. Blood feeding in the female A. aegypti mosquito is essential for egg maturation and for transmission of disease agents between human subjects. Here, we identify the A. aegypti sulfakinin receptor gene SKR from the A. aegypti genome and show that SKR is expressed at different developmental stages and in varied anatomical localizations in the adult mosquito (at three days after eclosion), with particularly high expression in the CNS. Knockingdown sulfakinin and sulfakinin receptor gene expression in the female A. aegypti results in increased blood meal intake, but microinjection in the thorax of the sulfakinin peptide 1 and 2 both inhibits dose dependently blood meal intake (and delays the time course of blood intake), which is reversible with receptor antagonist. Sulfakinin receptor expressed ectopically in mammalian cells CHO‐K1 responds to sulfakinin stimulation with persistent calcium spikes, blockable with receptor antagonist. These data together suggest that activation of the Gq protein‐coupled (i.e., calcium‐mobilizing) sulfakinin receptor inhibits blood meal intake in female A. aegypti mosquitoes and could serve as a strategic node for the future control of A. aegypti mosquito reproduction/population and disease transmission. Knockingdown of sulfakinin (SK) or sulfakinin receptor (SKR) gene with interference RNA (RNAi) increases, but injection of sulfakinin peptide (SK1 or SK2) decreases the blood meal intake in the mosquito Aedes aegypti. Sulfakinin stimulation of the mosquito A. aegypti sulfakinin receptor expressed in mammalian cells CHO‐K1 triggers cytosolic calcium oscillations. Activation of the Gq protein‐coupled sulfakinin receptor therefore inhibits blood meal intake in the mosquito A. aegypti; this could potentially be used to control both mosquito reproduction and disease transmission.